Velo 2nd gear, bicycle culture and style. - Ehmann, Sven; Klanten, Robert (Gestalten, 2013)
Choosing to ride a particular bike conveys an attitude and a way of life. Velo—2nd Gear illuminates and celebrates contemporary bicycle culture’s diverse scenes. From classic racing bikes to high-tech speed machines, from rough fixies to fashionable city cruisers and hardworking cargo bikes, this book showcases today’s most outstanding and unusual bicycles and their riders.Velo—2nd Gear not only introduces coveted manufacturers, specialized boutiques, and historical tours. It also explains how each bike-related scene cultivates its own distinct codes through the choice of certain frames, jerseys, caps, or bags or by visiting specific events or key establishments. In doing so, the book shows why, for more and more people, bicycles have now replaced cars as the vehicles that best express their identity.
Adlib record nr. 530011048
Engels
boek
Keywords: hedendaagse tijd